Architectural shop drawing of mock-up sample of CC5 concrete wall (RFA-414_Rev A) - BUCG-ABC Joint Venture (BUCG-ABC JV) (Brac University, 2023)
This record contains architectural contractor shop drawings of Brac University New Campus Project. It consists of PDF version of drawings.